2011
DOI: 10.1097/tp.0b013e3182313e4f
|View full text |Cite
|
Sign up to set email alerts
|

Thymoglobulin Versus Basiliximab Induction Therapy for Simultaneous Kidney-Pancreas Transplantation: Impact on Rejection, Graft Function, and Long-Term Outcome

Abstract: ATG versus basiliximab induction therapy results in decreased acute cellular rejection in the first year after SPK with similar side effects. Long-term graft function and survival are not affected by induction regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 14 publications
4
23
1
3
Order By: Relevance
“…Now, few studies have been published comparing these drugs. Bazerbachi et al found identical 1-year, 3-year, and 5-year pancreas survival rates between basiliximab and ATG (93% versus 90%, 89% versus 87%, and 83% versus 78%, respectively) [5]. Similarly, in our institution, no difference was detected in pancreas graft survival after 1, 3, and 5 years.…”
Section: Discussionsupporting
confidence: 66%
“…Now, few studies have been published comparing these drugs. Bazerbachi et al found identical 1-year, 3-year, and 5-year pancreas survival rates between basiliximab and ATG (93% versus 90%, 89% versus 87%, and 83% versus 78%, respectively) [5]. Similarly, in our institution, no difference was detected in pancreas graft survival after 1, 3, and 5 years.…”
Section: Discussionsupporting
confidence: 66%
“…Prednisone was used in pancreas transplant recipients, but since it could be tapered off in most patients during the first 2-3 years of follow-up or at least could be reduced to low dosages, a relevant impact on glycemic control is unlikely. Published data on induction therapy suggest that induction therapy with thymoglobulin is superior compared with other options (17,18). In our cohort, thymoglobulin induction therapy was only started in 2012; therefore, protocol changes in induction therapy were not influencing long-term outcome.…”
Section: Discussionmentioning
confidence: 78%
“…Induction therapy was performed initially with basiliximab (Novartis Pharma, Basel, Switzerland), and after 2012 with thymoglobulin (Sanofi, Paris, France) (17). Target long-term trough levels for tacrolimus were 10-15 mg/L.…”
Section: Immunosuppressionmentioning
confidence: 99%
“…Az Amerikai Egyesült Államokban 2007-ben az összes átültetett hasnyálmirigy 8,8%-a 2-es típusú cukorbetegbe került [9,10]. Nem egy esetben előfordul, hogy csak a C-peptid-mérés képes különbséget tenni az 1-es és 2-es típusú cukorbetegség között, mert egyébként a klinikai kép nagyon hasonló lehet mindkét típus esetében [11].…”
Section: Indikációunclassified